Supplementing Extraoperative Electrocorticography With Real-Time Intraoperative Recordings Using the Same Chronically Implanted Electrodes. Issue 6 (8th February 2021) - Warsi, Nebras M; Narvacan, Karl; Donner, Elizabeth; Go, Cristina; Strantzas, Samuel; Ochi, Ayako; Otsubo, Hiroshi; Sharma, Roy; Snead, O Carter; Ibrahim, George M
Abstract: BACKGROUND: The practice of intraoperative electrocorticography (iECoG) to guide resective epilepsy surgery is variable. Limitations of iECoG include variability in recordings from previously unsampled cortex, increased operative time and cost, and a lack of clear benefit to surgical decision-making. OBJECTIVE: To describe a simple technique to supplement extraoperative intracranial recordings with real-time iECoG using the same chronically implanted electrodes that overcome some of these limitations. METHODS: We describe the technical procedure, intraoperative findings, and outcomes of 7 consecutive children undergoing 2-stage resective epilepsy surgery with invasive subdural grid monitoring between January 2017 and December 2019. All children underwent placement of subdural grids, strips, and depth electrodes. Planned neocortical resection was based on extraoperative mapping of ictal and interictal recordings. During resection in the second stage, the same electrodes were used to perform real-time iECoG. RESULTS: Real-time iECoG using this technique leads to modification of resection for 2 of the 7 children. The first was extended due to an electroencephalographic seizure from a distant electrode not part of the original resection plan. The second was restricted due to attenuation of epileptiform activity following a partial resection, thereby limiting the extent of a Rolandic resection. No infections or other adverse events were encountered. CONCLUSION: We report a simple technique to leverage chronically implanted electrodes for real-time iECoG during 2-stage resective surgery. This technique presents fewer limitations than traditional approaches and may alter intraoperative decision-making.